Reinforced concrete wide beams under normal and high shear loading - Rao, G. Papa; Murty, D.S.R.; Rao, T. Umamaheswara; Mounisha, Y. (Journal of Structural Engineering, 2024)
Along with commonly occurring Reinforced Concrete (RC) narrow normal beams, RC wide beams also find place indifferent kinds of structures. Wide beams have width to depth ratios more than one. The shear strength of normal RCbeams with well distributed shear reinforcement along the span can be safely predicted by many national codes. Butin wide beams, not only, the shear reinforcement demand has to be satisfied along the span, but also, across the beamwidth, adequate number of vertical legs have to be provided in each stirrup. Tests in this investigation were conductedon five RC wide beams; two beams had low shear stress, while three beams had high shear stress. The test specimenswere 1700mm long, 250mm deep and 600mm wide. For all the beams the width to depth ratio was 2.4. In the two lowshear stress beams, the stirrup legs varied from two to four. The three high shear stress beams HSB1, HSB2 and HSB3had 2, 4 and 6 stirrup vertical legs respectively. In the two series of beams, the stirrups satisfy the requirements spanwise and width wise. Exhaustive investigation, undertaken herein on wide beams, revealed several significant findings,for useful adoption by structural engineers. Among the many conclusions one is, for the realisation of design shearforce, the spacing of stirrup legs across the width should be limited to lesser of effective depth and 300mm, for lowshear stress, for beams with high shear stress, leg spacing should not exceed effective depth/2.